Simulation of Ship Movement after Steering System Failure to Determine the Worst Case Scenario of Grounding - Mohović, Đani; Mohović, Robert; Rudan, Igor (Promet - Traffic&Transportation, 2013)
Ship grounding is one of the primary maritime navigation casualties and a result of an error made by the navigating officer, of a technical failure on vital ship equipment or of force majeure. In order to decrease the risk of grounding in such cases, this paper explores the ship movement during navigation when an extraordinary event occurs, such as steering system failure that affects the vessel’s direction directly and speed indirectly. One way to determine the ship movement in such circumstances is by simulating the ship movement on the navigational simulator according to the predefined scenarios, as explained in this paper. A total of 60 scenarios were researched, in the process of which ship type, ship size, ship speed and rudder deflection angle were varied. During the simulation, all relevant data concerning current movement of the ship and a graphical display of the performed simulation were recorded every 30 seconds. On the basis of the simulation results it is possible to determine the worst case scenario which can be used to define the consequence of grounding, one of the parameters necessary for the assessment of the risk of grounding.